Zn(TFSI)2-Mediated Ring-Opening Polymerization for Electrolyte Engineering Toward Stable Aqueous Zinc Metal Batteries - Zhenjie Liu; Murong Xi; Rui Sheng; Yudai Huang; Juan Ding; Zhouliang Tan; Jiapei Li; Wenjun Zhang; Yonggang Wang (Nano-Micro Letters)
Highlights A novel electrolyte enabled by Zn(TFSI)2-mediated ring-opening polymerization strategy for highly reversible aqueous zinc metal batteries was proposed. The novel electrolyte has good antioxidant stability and non-inflammability. The novel electrolyte widens the electrochemical window, improves the low-temperature performance, and inhibits Zn dendrite. The Zn metal anode shows an 8200 h lifespan at 1 mAh cm−2 and a 2500 h lifespan at 60% depth of discharge.